2002
DOI: 10.1149/1.1485807
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mechanical Polishing of Gallium Nitride

Abstract: Chemical mechanical polishing of gallium nitride with collodial silica has been demonstrated. Removal rates and ultimate surface roughnesses have been found to depend on sample polarity ͑either A or B faced͒ as well as the pH of the polishing fluid and the initial surface morphology. High quality A-faced samples exhibited no polishing action while B-faced material was readily removed. Removal rates at room temperature were found to vary from 0.4 to 1.1 m/h resulting in surface roughnesses as low as 1.1 nm root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 8 publications
1
50
0
Order By: Relevance
“…Tavernier et al reported CMP of polar GaN face by using Colloidal SiO 2 abrasive particles [13]. Gallium faced samples exhibited no polishing action and N-faced material was readily removed.…”
Section: Introductionmentioning
confidence: 99%
“…Tavernier et al reported CMP of polar GaN face by using Colloidal SiO 2 abrasive particles [13]. Gallium faced samples exhibited no polishing action and N-faced material was readily removed.…”
Section: Introductionmentioning
confidence: 99%
“…In chemical mechanical polishing ͑CMP͒ studies of GaN, the N-face polishing rate can be as fast as 1.1 m per hour, while no obvious polishing was observed on the as-grown Ga face. 15 Lithographic patterning and MBE regrowth was used to define different lateral regions of Ga-and N-terminated GaN. 10 These regions also exhibited large difference in etch rate in a KOH solution.…”
mentioning
confidence: 99%
“…In addition, 71 min is required for CMP to remove up to the same depth as that removed by RIE from the entire surface of the substrate in 1 min when the machining rate of CMP is 1100 nm/h. [3] Plasma CVM appears to be more suitable for high-speed processing than CMP.…”
Section: Comparison With Other Machining Methodsmentioning
confidence: 99%
“…[1,2] The surface of the bulk GaN substrate is finished by a polishing technique such as chemical mechanical polishing (CMP). [3] GaN is a very hard material; its Poisson ratio, Young's modulus, and Vickers hardness are 0.23, 290, and 12 GPa, respectively. [4,5] Generally, it is difficult to avoid damaging the bulk GaN substrate during surface polishing.…”
Section: Introductionmentioning
confidence: 99%